Real-Time Polarization-Resolved Imaging of Living Tissues Based on Two-Photon Excitation Spinning-Disk Confocal Microscopy - Goto, Ai; Otomo, Kohei; Nemoto, Tomomi (Frontiers in Physics, 2019)
Laser scanning microscopy using high-peak-power ultrashort near infrared light pulses can visualize biological microstructures by utilizing non-linear optical processes, such as multi-photon excitation and sum frequency generation. Here we introduced a polarization-resolving detection methodology for a laser scanning microscopy system equipped with a spinning-disk confocal scanner. The developed system achieved high-speed intravital imaging of living tissues with resolving their signals to orthogonally polarized components. First, we applied the system to a liposomal vesicle labeled with the fluorescent lipophilic dye and confirmed the orientation map of the lipid bilayer. Next, by detecting polarization-resolved second harmonic generation signals, the structural orientations of the collagen fibers in fixed mouse tissues were visualized without exogenous or genetic fluorophore labeling. Finally, we demonstrated in vivo polarization-resolved second harmonic generation imaging of the collagen fibers in the mouse skeletal muscles at a 56 Hz temporal resolution. We expect that our developed methodology can achieve real-time visualization, thus, revealing the conformational changes of supramolecular structures in living animals.